Imaging in Nuclear Medicine - Giussani, Augusto; Hoeschen, Christoph (Springer Berlin Heidelberg : Imprint: Springer, 2013)
This volume addresses a wide range of issues in the field of nuclear medicine imaging, with an emphasis on the latest research findings. Initial chapters set the scene by considering the role of imaging in nuclear medicine from the medical perspective and discussing the implications of novel agents and applications for imaging. The physics at the basis of the most modern imaging systems is described, and the reader is introduced to the latest advances in image reconstruction and noise correction. Various novel concepts are then discussed, including those developed within the framework of the EURATOM FP7 MADEIRA research project on the optimization of imaging procedures in order to permit a reduction in the radiation dose to healthy tissues. Advances in quality control and quality assurance are covered, and the book concludes by listing rules of thumb for imaging that will be of use to both beginners and experienced researchers.